Atuação fonoaudiológica em cuidados paliativos pediátricos e seus resultados na percepção de cuidadores e profissionais da equipe de um hospital universitário - Vanessa Giovannini Gomes Cunha (2016)
Objectives: To identify and present the main results of the articles that describe the perception of caregivers and care teams of professionals as much as palliative care for pediatric patients and to describe and analyze the speech therapy in pediatric cases in palliative care from a university hospital and its results in the perception of some professional support staff and caregivers. Methods: This study was structured in two stages: In the first, an integrative literature review was performed with literature in BIREME portal for the access to scientific databases LILACS and IBECS and PUBMED portal for the access to journals indexed on MEDLINE. Inclusion criteria were: original and cover aspects of palliative care, pediatrics and perception of caregivers and care teams of professionals. A descriptive analysis of the characteristics of the studies was performed and the information was organized according to the categories of analysis: quality of life promotion, treatment plans, expectations, emotional and spiritual aspects, communication, teamwork and the main difficulties experienced by caregivers and professionals. The second stage consisted of an analytical observational cross-sectional study, whose population consisted of patients in palliative care aged 1 day to 17 years and 11 months, admitted in that hospital and referred to the speech therapy service, and their caregivers and professionals who accompanied them. Data were collected from patient files and from questionnaires given to caregivers and staff professionals. It was performed the descriptive analysis of the informations and the analysis of agreement between the perceptions of caregivers and nutritionists. Results: In the first study, among the articles 541 located for screening, 23 were selected for full reading and 10 articles were included in the final analysis. In the second study, the oral motor sensory stimulation, the adequacy of the approach, the feeding tube and guidance for the stimulation of language was the most used phono-audiological procedures. There were a relevant number of patients with decreased saliva aspiration risk and during food consumption from speech therapy, according to the perception of caregivers and most professionals. In communications, there was improvement in a significant number of patients in the caregivers vision and in the perception of the professionals; there was an increase in the number of cases. A strong relationship of speech therapy service with nutritionists was observed in the treatment of feeding, and with the physiotherapists to deal with swallowing. A fragile link was identified with occupational therapists in relation to the worked aspects. The positive perception of the caregivers was relevant to the quality of life of pediatric patients in palliative care from speech therapy and was found in good agreement between the perceptions of nutritionists and caregivers.Conclusions: Some peculiarities in palliative care, extended to pediatrics, were revealed from the perception of caregivers and professionals. The instrumentalization of both is an important issue so as to cope with the limited living conditions of children and teenagers. It was also concluded that the results of speech therapy in pediatric palliative care are perceived by professionals and caregivers as favorable to the majority of patients in the aspects of swallowing saliva and feeding, besides reducing suffering and improving their quality of life.